2008
DOI: 10.1007/s11144-008-5253-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nickel loading on the activity of Ni/ZrO2 for methane steam reforming at low temperature

Abstract: The effect of Ni loading on the catalytic activity of Ni/ZrO 2 catalyst for methane steam reforming was investigated. The sample containing 15 wt.% Ni exhibited the highest activity as well as stability at 600 o C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 10 publications
0
7
1
4
Order By: Relevance
“…It should be noted, however, that even though the GHSV of 30,000 h −1 is the lowest applied in this study, it is higher than that reported in similar work in literature [15,23,[50][51][52], considering also that no diluent gas (He or N 2 ) is fed into the reactor during the reforming tests. The fact that most of the proposed catalysts approach equilibrium conversion under these conditions, indicate their high activity in the low temperature range.…”
Section: Methane Steam Reformingcontrasting
confidence: 58%
“…It should be noted, however, that even though the GHSV of 30,000 h −1 is the lowest applied in this study, it is higher than that reported in similar work in literature [15,23,[50][51][52], considering also that no diluent gas (He or N 2 ) is fed into the reactor during the reforming tests. The fact that most of the proposed catalysts approach equilibrium conversion under these conditions, indicate their high activity in the low temperature range.…”
Section: Methane Steam Reformingcontrasting
confidence: 58%
“…Various alternatives have been proposed to reduce the carbon deposition and improve the catalytic performance: (i) variation of preparation method of catalysts to modify the metal-support interaction [4][5][6]; (ii) variation of the crystallite size of the catalytic phase [7][8][9]; (iii) the use of solid-solution as catalytic support [10][11][12]. Additionally, the addition of basic oxides (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Category 2 shows the published work studying the influence of metal loading in other Ni based catalysts with different raw materials. The authors [33,34] investigated the effect of Ni loading in methane steam reforming, while Li et al studied the influence of nickel in acetic acid steam reforming [17].…”
Section: Introductionmentioning
confidence: 99%